2022
DOI: 10.3390/cancers14040988
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Venous Thromboembolism in Female Patients Undergoing Breast Surgery

Abstract: Albeit it does not have the highest venous thromboembolism (VTE) incidence compared to other neoplasms, breast cancer contributes to many VTE events because it is the most diagnosed tumor in women. We aim to analyze the occurrence and timing of VTE during the follow-up of patients who underwent breast surgery, the possible correlated factors, and the overall survival. This retrospective study included all female patients diagnosed with mammary pathology and surgically treated in our clinic between January 2002… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 60 publications
3
6
1
Order By: Relevance
“…Besides, we also found significant statistic differences in hypertension ratio and intraoperative hypotension time between the two groups. Although no significant statistic difference found in hypertension from multivariate logistic regression, a recent published study pointed invasive cancer, chronic hypertension, cancer type, and evidence of metastasis were the most significant risk factors for VTE in women who underwent breast surgery [22]. And a study aimed to assess the relationship between cardiovascular disease and the occurrence of VTE found that hypertension increased the risk of VTE in patients with newly diagnosed lung cancer, which may be mediated by inflammation [23].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, we also found significant statistic differences in hypertension ratio and intraoperative hypotension time between the two groups. Although no significant statistic difference found in hypertension from multivariate logistic regression, a recent published study pointed invasive cancer, chronic hypertension, cancer type, and evidence of metastasis were the most significant risk factors for VTE in women who underwent breast surgery [22]. And a study aimed to assess the relationship between cardiovascular disease and the occurrence of VTE found that hypertension increased the risk of VTE in patients with newly diagnosed lung cancer, which may be mediated by inflammation [23].…”
Section: Discussionmentioning
confidence: 99%
“…Our research found that age, temperature, amount of blood loss, PICC, chemotherapy, anemia, INR, and CA199 were independent risk factors for VTE, which was not exactly the same as previous studies. 10 , 13 , 22 , 32 PICC was recognized as an independent risk factor for thrombosis, the behavior leads to a hypercoagulable state of the blood and increases the risk of thrombosis by disrupting the Virchow triad. 23 , 24 Chemotherapeutic drugs can inhibit the synthesis of prostacylin, thrombomodulin, heparan sulfate, tissue factor pathway inhibitors, and plasminogen activator, thus facilitating the formation of venous thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] A study of 5039 women who underwent breast surgery found that chronic hypertension, high body mass index, cancer type, and evidence of metastasis turned out to be the most significant risk factors for VTE. 13 A study had showed that independent predictors for VTE in metastatic CRC included female sex, African American race, prior VTE history, and right sided cancers. 14 However, there has not been a unified conclusion on the risk factors of VTE in inpatients with CRC in China and our study explored it to aid clinical prevention and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Among women who underwent breast surgery, chronic hypertension, high body mass index (BMI), cancer type, and evidence of metastasis were noted as the most significant risk factors for VTE, while type of breast surgery, type of axilla surgery, type of plastic surgery did not increase risk of VTE [25]. Also, hospital length of stay >3 days, and general anesthesia were noted as risk factors of developing VTE in patients undergoing reconstructive BC surgery [26].…”
Section: Surgerymentioning
confidence: 99%